ETNOMATEMATIKA DALAM TARI JEPIN TALI BUI MASYARAKAT MELAYU PONTIANAK - Rinni Sari Darmayanthi; Agung Hartoyo; Silvia Sayu (Universitas Tanjungpura, 2020)
Abstract The aim of this study was to determine the range of movements used in the Jepin Tali Bui Dance Pontianak Malay Community and to determine the ethnomatemics contained in the Tali Bui Jepin Dance. The method used is qualitative in the form of case study research. The subject of this research is a former senior dancer, dance studio owner and dance trainer and the focus is on the Pontianak Malay community who have an interesting tradition of Jepin Tali Bui Dance. In general, the Jepin Tali Bui dance is performed by seven dancers, has some motion salts namely hanging steps, cease steps and oblique steps, and also has a number of tie patterns, such as woven mats, woven mats and woven mats. The results of the data analysis show that there is a mathematical element in the Tali Bui Jepin Dance based on the age of the Tali Bui Jepin Dance from the first time entering Pontianak, the anniversary of Pontianak City, the value of compactness and togetherness value, grouping of dance attributes, the number of straps used, the number of ropes used, the musical instruments used, the pattern floor, lock pattern 1-7, time needed to perform the dance, hanging steps, cease steps, and oblique steps. Keywords: Ethnomatematics, Jepin Tali Bui Dance, Pontianak Malay Culture